The Pragmatics of Love Text Messages among University of Uyo Students - Esther Ekom Robert (European Scientific Journal, ESJ, 2022)
In line with the trends in media and pragmatic discourse, studies on texting have been examined, focusing on the creative utilization of language resources as well as their contextual cues. The purpose of this paper is to examine the socio-pragmatic manifestations of love and gender differences in the love text messages of the University of Uyo students. Specifically, the objective of the paper is to confirm whether or not the differences are statistically significant and culturally conditioned. Thus, adopting quantitative analytical methods (chi-square and percentages), the analysis is anchored on the socio-pragmatic theory of Leech (1983) and supplemented by Thurlow and Brown’s (2003) romantic and sexual orientations. Twenty (10 male and 10 female) students of the Faculty of Arts supplied their two most preferred love text messages. The data are categorized according to thematic frames of Love Reiteration (LR), Wooing (Wg), Love Wordplay (LW), and Sexual Behaviour (SB). The results indicate that LR texts were the most preferred (18/45%), while SB texts were the least preferred (5/12.5%). Again, whereas the male students preferred both LR and Wg texts most (6/31.6%) and LW texts least (3/15.7%), the female ones loved LR texts most (12/57.1%) and SB texts least (1/4.8%). Thus, the chi-square quantitative analysis of the results shows that the differences in the text preferences are significant. The paper submits that the University of Uyo students’ love text preferences affirm the second-wave feminist linguistic typology of socio-cultural differences in the language use of men and women in Nigeria. Again, the findings have revealed interesting and varied ideologies about how women and men ought to speak in their speech communities. Based on the conclusion, it is recommended that further socio-pragmatics research be carried out in other tertiary institutions, preferably in the South Eastern and Northern parts of Nigeria or schools outside Nigeria, but beaming research light on the socio-pragmatics of age and status differences as well as differences in the students’ years of study.